2015
DOI: 10.1021/acs.inorgchem.5b01437
|View full text |Cite
|
Sign up to set email alerts
|

A Switchable Molecular Dielectric with Two Sequential Reversible Phase Transitions: [(CH3)4P]4[Mn(SCN)6]

Abstract: A new organic-inorganic hybrid switchable and tunable dielectric compound, [(CH3)4P]4[Mn(SCN)6] (1), exhibits three distinct dielectric states above room temperature and undergoes two reversible solid-state phase transitions, including a structural phase transition at 330 K and a ferroelastic phase transition with the Aizu notation of mmmF2/m at 352 K. The variable-temperature structural analyses disclose that the origin of the phase transitions and dielectric anomalies can be ascribed to the reorientation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Recently, an effective strategy to design new NLO switches is to construct and screen phase-transition materials associated with the transformation from a centrosymmetric structure to a noncentrosymmetric one. Several simple organic salts, inorganic–organic hybrids and a recent plastic crystal have been reported to be potential NLO switches. Among them, inorganic–organic hybrids afford an important opportunity to integrate phase transition with multiple switching responses. Compared to the pure organic or inorganic compounds, inorganic–organic hybrids combine the best aspects of inorganic frameworks and organic molecules into a monocrystal structure to achieve multifunctional characteristics. Particularly, the hybrids with ABX 3 -type perovskite structures (where A is the molecular cation, B is the metal ion, and X is the bridging ligand, e.g., X – , CN – , HCOO – , N 3 – ) have been discovered with remarkable multifunctional properties such as photovoltaic, optical, electric, and magnetic properties. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, an effective strategy to design new NLO switches is to construct and screen phase-transition materials associated with the transformation from a centrosymmetric structure to a noncentrosymmetric one. Several simple organic salts, inorganic–organic hybrids and a recent plastic crystal have been reported to be potential NLO switches. Among them, inorganic–organic hybrids afford an important opportunity to integrate phase transition with multiple switching responses. Compared to the pure organic or inorganic compounds, inorganic–organic hybrids combine the best aspects of inorganic frameworks and organic molecules into a monocrystal structure to achieve multifunctional characteristics. Particularly, the hybrids with ABX 3 -type perovskite structures (where A is the molecular cation, B is the metal ion, and X is the bridging ligand, e.g., X – , CN – , HCOO – , N 3 – ) have been discovered with remarkable multifunctional properties such as photovoltaic, optical, electric, and magnetic properties. …”
Section: Introductionmentioning
confidence: 99%
“…As asignificant physical property,the dielectric constant generally shows an observablec hange in the neighborhoodo ft he phase transition temperature. [1,2,4,13,14,17,18,31,[33][34][35][36][37][38][39][40][41] The dielectric constant,d ependence on temperature of the pressed sample, was measured under the action of the electric field with af re-quencyof1 00 kHz in the heating/cooling circulatory process.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…There are a few compounds reported that are built up of discrete anionic manganate(II) complexes, in which the Mn II atoms are in an octahedral coordination by six terminal N-bonding thiocyanate ligands with different chargecompensating cations. They include tetrakis(tetramethylphosphonium) [hexakis(thiocyanato)manganese(II)] (Li et al, 2015), tetrakis(tetramethylammonium) [hexakis(thiocyanato)manganese(II)] (Savard & Leznoff, 2013) and tetrakis(tris(aminoethyl)amine)(thiocyanato)copper(II) [hexakis(-thiocyanato)manganese(II)] (Bose et al, 2006). Similar compounds with five thiocyanate anions coordinating to Mn II are also known, but only a few have been reported (Matoga et al, 2015;Savard & Leznoff, 2013;Hill et al, 2008).…”
Section: Database Surveymentioning
confidence: 99%